Implikasi Pendidikan dari Al-Qur’an Surat Al-Kahfi Ayat 71-82 tentang Interaksi Nabi Musa dengan Nabi Khidir terhadap Komunikasi Interaksional - Putri Maryam F; Mujahid Rashid; Heru Pratikno (Bandung Conference Series: Islamic Education, 2023)
Abstract. The educational process is very dependent on the holder of the tool, namely the educators. However, the current reality is that there are not a few educators and managers of educational institutions who have not been able to improve their quality. One reason is the lack of knowledge of understanding the Qur'an. To restore these conditions, the efforts made are to provide an understanding of the Qur'an, one of which is by studying the Al-Qur'an surah Al-Kahf verses 71-82. From the statement above, the formulation of the problem is formed, namely: (1) What is the opinion of the mufassir about the Al-Qur'an surah Al-Kahf verses 71-82? (2) What is the essence of Surah Al-Kahf verses 71-82? (3) What is the theory of interactional communication according to experts? (4) What are the educational implications contained in Q.S. Al-Kahf verses 71-82 about the interaction between Prophet Musa and Prophet Khidir regarding interactional communication? The method used in this research is descriptive-analytical method. The technique used in data collection is the library research technique (library) researchers examine in depth the interpretations related to research problems. From this research, it was obtained the contents of QS Al-Kahf verses 71-82 that everything that happens must have a reason behind it, unresolved doubts and ignorance can lead to failure, Allah knows what we do not know, does good without strings attached, and it is not permissible for us to prejudice in advance about things we don't know the reasons for. The implications of Q.S Al-Kahf verses 71-82 are that before carrying out the learning process, educators should make agreements or establish regulations with students, in order to create an orderly and directed educational process, an educator should instill intentions in the heart while carrying out worship so that the educational process or teaching interactions are carried out sincerely without any strings attached, before carrying out the educational process the educator should inform the purpose of the educational process to be carried out, as a good student should not be prejudiced against things for which the reason is unknown, because everything must have a reason behind it. Abstrak. Proses pendidikan sangat bergantung pada pendidik. Namun kenyataannya kualitas pendidik dan pengelola lembaga pendidikan belum berkualitas baik. Salah satu penyebabnya adalah kurangnya pengetahuan untuk memahami Al-Qur'an. Untuk mengembalikan kondisi tersebut, maka dilakukan upaya pendalaman pemahaman Al-Qur'an, salah satunya dengan mempelajari Al-Qur'an Surah Al-Kahfi ayat 71-82. Dari pernyataan di atas maka tebentuk rumusan masalah yaitu: (1) Bagaimana pendapat para mufassir tentang Al-Qur’an surat Al-Kahfi ayat 71—82? (2) Bagaimana esensi dari surat Al-Kahfi ayat 71—82? (3) Bagaimana teori komunikasi interaksional menurut para ahli? (4) Apa implikasi pendidikan yang terkandung dalam Q.S. Al-Kahfi ayat 71-82 tentang interaksi antara Nabi Musa dengan Nabi Khidir terhadap komunikasi interaksional? Metode yang digunakan dalam penelitian ini adalah metode deskriptif-analitis. Dalam mengkaji peneliti menggunakan Teknik liberary research (kepustakaan) peneliti mengkaji secara mendalam dari tafsir yang berhubungan dengan masalah penelitian. Dari penelitian ini diperoleh isi kandungan QS Al-Kahfi ayat 71-82 bahwa segala sesuatu yang terjadi pasti memiliki alasan dibaliknya, keraguan dan ketidaktahuan yang tidak dipecahkan dapat menimbulkan kegagalan, Allah mengetahui hal yang tidak kita ketahui, melakukan kebaikan tanpa pamrih, serta tidak boleh berprasangka terlebih dahulu terhadap hal yang belum kita ketahui alasannya. Adapun implikasi dari Q.S Al-Kahfi ayat 71-82 yakni sebelum melaksanakan proses pembelajaran, pendidik hendaknya melakukan kesepakatan atau menetapkan peraturan dengan peserta didik, guna menciptakan proses pendidikan yang tertib dan terarah, seorang pendidik hendaknya menanamkan niat dalam hati sedang melaksanakan ibadah sehingga proses pendidikan atau interaksi pengajaran dilakukan secara ikhlas tanpa pamrih, sebelum melaksanakan proses pendidikan hendaknya pendidik menginformasikan tujuan dari proses pendidikan yang akan dilaksanakan, sebagai peserta didik yang baik sebaiknya tidak berprasangka terhadap hal yang belum diketahui alasannya, karena segala sesuatu pasti memiliki alasan dibaliknya.